Pola makanan pendamping air susu ibu dan status gizi bayi 0-12 bulan di Kecamatan Lhoknga Kabupaten Aceh Besar - Aripin Ahmad; Dradjat Boediman; Endy Paryanto Prawirohartono (Jurnal Gizi Klinik Indonesia, 2006)
Background: The prevalence of malnutrition in Indonesia is still high. One of potential factor contributing to the high prevalence of malnutrition is improper complementary feeding pattern and breast feeding practices. In the community there are three complementary feeding patterns; those are traditional feeding, industries feeding and combination.Objective: This study was conducted to analyze the association between complementary feeding, energy and protein intake, and breast feeding status with nutritional status of infants 0-12 month old.Method: This study used a cross sectional design. Subjects were 151 infants 0-12 month old. Complementary feeding pattern and breast feeding status were collected using interview methods. Energy and protein intakes were collected using food recall methods. Nutritional status was measured using weight for length (WHZ). The chi square test was used to analyze the data.Result: There wasn’t any association between complementary feeding pattern and nutritional status of infants 0-6 m.o. old (p=0.04) and 6-12 month (p=0.62). There wasn’t any association between energy intake and nutritional status of infants 0-6 month old (p=0.40), but there was any association in infants 6-12 month old (p=0.01). Protein intake associated with nutritional status of infants 0-6 m.o. old and 6-12 month old (p=0.033 and p=0.04). Breast feeding status didn’t associated with nutritional status of infants 0-6 month old and 6-12 month old (p=0.689 and p=0.10).Conclusion: Complementary pattern and breast feeding status were not associated with nutritional status. Energy intake was associated with nutritional status of infants 6-12 month old. Protein intake associated with nutritional status of infants 0-6 month old and 6-12 month old.